Detoxification of deoxynivalenol by pathogen-inducible tau-class glutathione transferases from wheat - Michlmayr, Herbert; Siller, Martin; Kenjeric, Lidija; Doppler, Maria; Malachova, Alexandra; Hofer, Manuel; Hametner, Christian; Schweiger, Wolfgang; Steiner, Barbara; Kugler, Karl G.; Mayer, Klaus F.X.; Buerstmayr, Hermann; et al. (Elsevier BV, 2026)
Deoxynivalenol (DON) is a toxicologically relevant trichothecene mycotoxin frequently found in cereal products. It is a virulence factor produced by the plant pathogen Fusarium graminearum during cereal crop infections. Investigating plant defense mechanisms is crucial for understanding plant resistance to F. graminearum and identifying new biocatalysts for DON detoxification. Previous studies identified DON-thiol adducts in cereal samples, indicating partial DON detoxification by glutathione transferases (GSTs). DON possesses two electrophilic centers for thiol conjugation, resulting in either epoxide opening at C13 or Michael addition at C10. At present, information on plant GSTs that catalyze these reactions is limited. In this study, Fusarium-inducible wheat GSTs were identified by analyzing the transcriptome of Fusarium-infected wheat heads. Twelve highly induced genes of the tau and phi GST classes were heterologously expressed and purified, biochemically characterized with model substrates, and assayed for activity with DON. Use of LC-MS showed that four of the selected tau class GSTs conjugated DON to GSH by epoxide opening (DON-13-GSH) and/or the reversible Michael addition reaction (DON-10-GSH). The crystal structure of a wheat GST (herein designated “TaGST-10”) in complex with DON-13-GSH was solved at a resolution of 2.3 Å and provided insights into the binding of DON at the active site of tau class GSTs. Our results corroborate the hypothesis that enzyme-catalyzed, GSH-mediated DON detoxification may be involved in plant response to Fusarium infection.